NMR crystallography: structure and properties of materials from solid-state nuclear magnetic resonance observables - Bryce, David L. (IUCrJ, 2017)
This topical review provides a brief overview of recent developments in NMR crystallography and related NMR approaches to studying the properties of molecular and ionic solids. Areas of complementarity with diffraction-based methods are underscored. These include the study of disordered systems, of dynamic systems, and other selected examples where NMR can provide unique insights. Highlights from the literature as well as recent work from my own group are discussed.